Tax Streams, Land Rents and Urban Land Allocation - Yugang Tang; Zhihao Su; Yilin Hou; Zhendong Yin (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines the fiscal motives behind municipal governments' decisions to allocate commercial and residential land when two categories of land use are subject to different fiscal revenue alternatives: business-related tax and/or land rent. We use urban parcel-level land transfers during China's peak period of urbanization, match commercial parcels with residential parcels, and find significant price discounts on commercial parcels relative to adjacent residential parcels. The observed discounts arise from the future tax flows from commercial use, i.e., expected taxes from developed commercial land reduce its transfer price. We conduct a structural estimation to examine the implications on land use structure of future taxes lowering land transfer prices. Results show that while prospective taxes increase commercial land supply, a significant portion of the favorable treatment impact is mitigated by market price responses, suggesting that the land market counters commercial land favoritism when local revenues include both business-related taxes and land value-based charges. The results have implications for the design of urban public revenue systems.
Keywords: O18; P48; R12; R31; R38; 330; fiscal incentives; land transfer; spatial matching; land use